LEARNING STRATEGIES FOR EFL STUDENTS IN DEVELOPING THEIR VOCABULARY MASTERY - Yusak Lestari Diyono (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2009)
Learning strategies are the deliberate actions that learners select and control to achieve desired goals or academic objectives. In the area of vocabulary mastery, learning strategies can be defined as various ways of all language learners to learn new vocabulary items in accordance with the learners’ needs and preferences. In learning a foreign language, choice of learning strategies is much influenced by or associated with a number of factors such as : language being learned, duration, degree of metacognitive awareness, age, sex, attitudes, personality characteristics, career orientation, language teaching methods, and task requirements. A more effective language learner is the one who uses better learning strategies and implements more appropriate strategies than do less effective learners in each of the main language skills.